2019
DOI: 10.1017/jfm.2018.995
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic path analysis of confinement influence on steady two-dimensional detonation propagation

Abstract: Steady detonation in multi-dimensional flow is controlled by the chemical energy release that occurs in a subsonic elliptic flow region known as the detonation driving zone (DDZ). It is the region encompassing the detonation shock and sonic flow locus (in the frame of the detonation shock). A detonation that is strongly confined by material surrounding the explosive has the shock and sonic locus separated at the material interface. Information about the material boundary is traditionally believed to influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A limiting HE C + characteristic, shown in figure 6(a), bounds the region of HE supersonic flow for which C + characteristics from the HE-SS boundary impinge on the sonic locus. This effect was recently identified by Chiquete & Short (2019), although they considered a specialised problem consisting only of the HE domain with an imposed HE-confiner interface shape. Here we show that the same behaviour occurs for multi-material flows where the confiner dynamics is accounted for.…”
Section: Stainless Steel Confinementmentioning
confidence: 81%
See 1 more Smart Citation
“…A limiting HE C + characteristic, shown in figure 6(a), bounds the region of HE supersonic flow for which C + characteristics from the HE-SS boundary impinge on the sonic locus. This effect was recently identified by Chiquete & Short (2019), although they considered a specialised problem consisting only of the HE domain with an imposed HE-confiner interface shape. Here we show that the same behaviour occurs for multi-material flows where the confiner dynamics is accounted for.…”
Section: Stainless Steel Confinementmentioning
confidence: 81%
“…Bdzil (1981), Stewart & Bdzil (1989), Vidal et al (1994), Gamezo & Oran (1997), Sharpe & Braithwaite (2005), Schoch, Nikiforakis & Lee (2013) and . Information about the confinement flow is transmitted to the subsonic DDZ region across the HE-confiner material interface, although Chiquete & Short (2019) have recently shown that propagation of information through the supersonic flow region in the HE, originating at the confinement boundary downstream of the DDZ, can also influence the DDZ structure. For higher density metal or alloy confiners, such as tantalum or stainless steel (SS), an oblique inert shock is transmitted into the confiner.…”
Section: Introductionmentioning
confidence: 99%
“…The lower flow velocity due to viscosity in a boundary layer acts as a mass sink that induces locally a specific mass larger than in the entire cross-section. The consequences are a diverging flow and, therefore, a curvature and a velocity deficit of the average front [64][65][66], that should increase with increasing thickness of the boundary layer. This description applies to cellular detonations if the cell widths are small enough compared to the transverse dimensions of the tubes so that a smooth average surface represents well the detonation front.…”
Section: Cell Patterns and Cross-section Shapes And Areasmentioning
confidence: 99%
“…Although there are certain differences in the detonation structures between twodimensional and three-dimensional simulations, 45 the two-dimensional simulation can also well represent the initiation and propagation process of the detonation wave. 46 The typical methods for shock-capturing introduce considerable numerical dissipation, which disturbs the physical diffusion part of the NS equations. To analyse the complex structure of flow field with the inclusion of various shock waves more accurately, the hybrid sixth-order weighted essentially non-oscillatory centered difference (WENO-CD) scheme 47,48 is utilised to solve the NS equations with chemical reaction.…”
Section: Governing Equations and Numerical Schemementioning
confidence: 99%